From Biomass to Biobased Products (IntechOpen, 2024)
Realizing the finite nature of natural resources such as fossil fuels, the emphasis is now shifting to alternative raw materials with the potential to mitigate the environmental, economic, and social stresses of today’s world. Under this horizon, in this book, we explore the use of biomass and key issues, including technological nodes and disruptive technologies capable of unlocking the black box of biomass-based technology. This book provides an overview for those attentive to the promises of biomass as a source of a myriad of specialty products.